Does customer incivility undermine employees' service performance?. (August 2020) - Cheng, Bao; Dong, Yun; Zhou, Xing; Guo, Gongxing; Peng, Yan
Highlights: Customer incivility negatively influenced PCSP, it did not impact in-role performance. Negative affectivity mediated the relation of customer incivility and proactive customer service performance. Hostile attribution bias moderated the relation of customer incivility and negative affectivity. Conservation of resources theory provided the theoretical foundation. Time-lagged research was conducted and data were collected from frontline hotel employees and their supervisors. Abstract: This study extends the growing body of research on customer incivility by examining its impact on employees' in-role and extra-role service performance in the hospitality industry. Using a sample of 307 employee–supervisor dyads in nine hotels in Zhuhai City, China, this research examined the impact of customer incivility along with negative affectivity and hostile attribution bias on in-role performance and extra-role performance, particularly proactive customer service performance (PCSP). The results demonstrate that, while customer incivility negatively influenced PCSP, it did not impact in-role performance. Furthermore, the effect of customer incivility on PCSP was mediated by negative affectivity. Additionally, hostile attribution bias significantly moderated the relationship between customer incivility and negative affectivity, as well as the indirect relationship between customer incivility and PCSP through negative affectivity.